Coexistence of Granular Cell Tumor and Invasive Ductal Breast Cancer in Contralateral Breasts: A Case Report - Di Bonito, Maurizio (MDPI, 2014)
Granular cell tumor (GCT) is a benign tumor of the breast that can mimic, on breast imaging, invasive carcinomas. Biological evolution of mammary GCT is unknown, especially if it is associated with an invasive carcinoma in the same or contralateral breast. This report details the morphological features of these synchronous lesions highlighting their biological characteristics and suggesting an appropriate follow up.